The Impact of Good Corporate Governance Mechanism and Firm Size on Earnings Management - Novia Sari Tanjung; Barlia Annis Syahzuni (Lafadz Jaya Publisher, 2023)
This study aims to investigate the mechanism of company management based on the indicators of the Board of Directors by proxy comparing the total members of the company's board of directors with the number specified in the Financial Services Authority Regulations, Independent Commissioners by proxy dividing the percentage of total independent commissioners and total company commissioners, Audit committee meetings are proxied based on the frequency of meetings held by the audit committee and Audit Committee Expertise is measured by calculating the proportion of audit committee members who have expertise in finance and accounting, and Firm size is measured based on the company's total assets to observe the impact on Earning management. It focuses on conventional banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 - 2022. Multiple linear regression was apanalysiso analyzed with the help of SPSS statistical software. The population of this research consists of 28 entities selected by purposive sampling method. The findings of this study reveal that the Board of Directors has a significant negative correlation with Earning management. However, the existence of an Independent Commissioner, the frequency of meetings and the expertise of the Audit Committee have not been able to significantly affect management's earnings. Conversely, firm size is positively correlated with earning management.